Examining the Relationship between Water-Equivalent Diameter (Dw) and Body Mass in Breast Cancer Patients - Nurhanivah, Devi; Ramdhani, Saumi Zikriani; Bilqis, Ayesha (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
Breast cancer is the most prevalent cancer worldwide, necessitating precise imaging techniques for effective treatment planning. This study aims to analyze the Water-Equivalent Diameter (Dw) in breast cancer patients using Computed Tomography (CT) and to investigate its relationship with patient body mass. Medical imaging data from 30 breast cancer patients, aged 23-66 years, was reviewed to calculate Dw using three different methods: contour ROI, elliptical ROI, and without ROI. The results showed average Dw values of 28.68 cm for contour ROI, 29.184 cm for elliptical ROI, and 30.255 cm without ROI. This indicates that contour ROI yields the smallest Dw due to its focus on cancerous areas. Furthermore, a positive linear correlation between Dw and body mass was established, with an R² value of 0.7743. This suggests that larger body mass leads to increased Dw values. This study emphasizes the importance of considering ROI selection and highlights the significant impact of patient body mass on Dw. This is crucial for optimizing radiation exposure in breast cancer treatment.